Guru Thoriqah Alawiyyin di Tanah Betawi Abad 20 - Aji Setiawan ST (The International Journal of Pegon : Islam Nusantara civilization, 2021)
Habib Abdurrahman as-Segaf is no stranger to the people around Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek). The owner of the complete greeting al-Walid al-Habib Abdurrahman bin Ahmad bin Abdul Qodir Assegaf is one of the important scholars who played a major role in the development of Islam in the metropolitan area. The figure born in 1908 in Cimanggu Bogor is known as a sincere educator. He dedicated his life to teaching his knowledge to the people. In fact, from a young age, he was believed to teach at Madrasah Jami'at al-Khair, the oldest formal Islamic educational institution in Batavia, at that time. The passion to fight to teach knowledge from al-Walid, as he is familiarly called, has crystallized when he was young. At the age of 20, he moved to Bukit Duri, South Jakarta. Armed with religious knowledge that had been obtained during his studies, he established his own educational institution named Tsaqafah Islamiyah. The institution that focuses on teaching religious science still survives until now in the midst of the hustle and bustle of Jakarta. Nama Habib Abdurrahman as-Segaf tak asing bagi masyarakat di sekitar Jakarta, Bogor, Depok, Tangerang, dan Bekasi (Jabodetabek). Pemilik sapaan lengkap al-Walid al-Habib Abdurrahman bin Ahmad bin Abdul Qodir Assegaf ini merupakan salah satu ulama penting yang berperan besar dalam perkembangan Islam di kawasan metropolitan tersebut. Tokoh kelahiran 1908 di Cimanggu Bogor ini dikenal sebagai pendidik yang tulus ikhlas. Ia mendedikasikan hidupnya untuk mengajarkan ilmunya kepada umat. Bahkan, sejak usianya masih muda, ia dipercaya mengajar di Madrasah Jami'at al-Khair, lembaga pendidikan Islam formal tertua yang ada di Batavia, ketika itu. Semangat untuk berjuang mengajarkan ilmu dari al-Walid, demikian ia akrab disapa, telah mengkristal saat usianya muda. Pada umur 20 tahun, ia hijrah ke Bukit Duri, Jakarta Selatan. Berbekal ilmu agama yang telah diperoleh selama menimba ilmu, ia mendirikan lembaga pendidikan sendiri yang diberi nama Tsaqafah Islamiyah. Lembaga yang fokus pada pengajaran ilmu agama itu masih tetap bertahan hingga kini di tengah-tengah hiruk pikuk Jakarta.